Inovasi Kurikulum Fikih pada Kurikulum Merdeka Perspektif Fethullah Gülen: Analisis terhadap Capaian Pembelajaran di Madrasah - Martarosa Maulidia; Hanun Asrohah; Husniyatus Salamah Zainiyati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study examines the relevance of Fiqh curriculum innovation within the Merdeka Curriculum in relation to Islamic educational thought espoused by Fethullah Gülen, particularly in the context of learning outcomes in Indonesian madrasahs. The primary aim is to identify the alignment between Gülen’s educational principles (which emphasize the integration of spiritual, intellectual, and social values) by the character based and contextual approach of the Merdeka Curriculum, especially in the subject of Fiqh within the madrasah environment. This research employs a qualitative library research method, analyzing curriculum documents (specifically the 2022 and 2024 decrees issued by the Directorate General of Islamic Education) alongside literature on Gülen’s educational philosophy. The findings indicate that the 2022 Fiqh Learning Outcomes are more compatible with Gülen’s framework than those of 2024, as they support the development of Higher Order Thinking Skills (HOTS), character formation, and social responsibility. Conversely, the 2024 outcomes tend to simplify the content and risk hindering the attainment of holistic competencies. The study concludes that the innovation of the Fiqh curriculum in madrasahs holds significant potential for shaping a religious, inclusive, and open-minded generation when integrated with the educational principles advocated by Fethullah Gülen.